Modification of Gene Expression Involved in Alkaloid Production in Opium Poppy by VIGS Combined With Pretreatment of Macerozyme Enzyme - Deniz Ece Özcan; Deniz Köm; Ozan Doğan; Semiha Erişen; Selma Onarici (Plant Direct)
ABSTRACT Papaver somniferum L., a medicinal plant renowned for its pharmaceutical alkaloids, has captivated scientific interest due to its rich secondary metabolite profile. This study explores a novel approach to manipulating alkaloid biosynthesis pathways by integrating virus‐induced gene silencing (VIGS) with macerozyme enzyme pretreatment. Targeting key genes in the benzylisoquinoline alkaloid (BIA) pathway (CODM, T6ODM, COR, DIOX2), the research aimed to elucidate the transformative potential of enzymatic preconditioning in somatic embryo cultures. To address the cell wall barrier, a known limitation in genetic manipulation, macerozyme pretreatment was employed, significantly enhancing gene silencing efficacy. Quantitative reverse transcription PCR analyses revealed significant alterations in gene expression profiles with macerozyme pretreatment, whereas no changes were observed in its absence. The T6ODM + DIOX combination was the most effective, reducing CODM, T6ODM, and DIOX2 expression by 72%, 65%, and 60%, respectively. Conversely, T6ODM expression increased by up to 107% in the CODM treatment. Notably, COR expression displayed dual regulatory dynamics, with suppression (47% decrease in T6ODM + DIOX) and enhancement (49% increase in CODM+DIOX) observed under different conditions. These findings underscore the complex interplay of gene regulation in the morphine biosynthesis pathway. This study highlights the critical role of macerozyme enzymatic pretreatment in overcoming cell wall barriers, enabling effective VIGS applications in somatic suspension cultures. The combination of VIGS and enzymatic pretreatment provides a robust platform for targeted metabolic engineering, offering insights into the regulation of morphine biosynthesis and paving the way for advancements in pharmaceutical alkaloid production and functional genomics in medicinal plants.